1991
DOI: 10.1161/01.atv.11.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Plasma triglyceride and coronary heart disease.

Abstract: Although the literature on epidemiological associations between plasma triglyceride and CHD is not completely consistent, trends do emerge from the studies described here. First, the majority of observational studies demonstrate a significant univariate relation, although the results of case-control and cross-sectional studies are more uniform than those from prospective study designs. In many but not all studies, triglyceride remains a significant predictor of CHD in multivariate statistical analyses after co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
60
0

Year Published

1993
1993
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 599 publications
(62 citation statements)
references
References 113 publications
2
60
0
Order By: Relevance
“…In our study level of serum VLDL was very significantly raised in cases (p<0.001). Studies have shown high risk of CAD in patients with increased serum TGL levels (11). Since VLDL carries the highest amount of TGL this may be the reason for very high level of VLDL in our study.…”
Section: Discussionsupporting
confidence: 48%
“…In our study level of serum VLDL was very significantly raised in cases (p<0.001). Studies have shown high risk of CAD in patients with increased serum TGL levels (11). Since VLDL carries the highest amount of TGL this may be the reason for very high level of VLDL in our study.…”
Section: Discussionsupporting
confidence: 48%
“…The results of multivariate statistical analyses including both triglycerides and HDL cholesterol may be difficult to interpret, due to the metabolic interrelationship between HDL and triglyceride-rich lipoproteins. Furthermore, the larger variability of triglyceride levels may result in an underestimation of the relationships between triglycerides and disease [25]. Measurements of fasting triglyceride levels can lower some of this variability, but people are in a nonfasting state most of their time, so fasting levels may not measure their exposure to triglycerides correctly.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of elevated plasma cholesterol as a risk factor for coronary heart disease is indisputable, but the role of triglyceride has been controversial for decades [1][2][3][4], and has been referred to as the "forgotten risk factor" [5]. Epidemiologic evidence now demonstrates that elevated triglyceride is associated with increased risk of cardiovascular disease (CVD), independent of high-density lipoprotein (HDL) cholesterol.…”
Section: Introductionmentioning
confidence: 99%